Dor no ombro e sua relação com a coluna cervical - FERREIRA, Milene Eloise Callegari (2019)
The first article had as objectives to verify if the cervical spine preferential direction exercise promotes immediate change in the activity and sequence of activation of the shoulder and shoulder girdle muscles in patients with shoulder pain and to verify if there is difference in the pattern of muscular activity and in the sequence of activation of these muscles between patients with pain complaints with and without the complementary exams diagnosis of shoulder dysfunction. We selected 14 individuals, who were separated into two groups: a group with pain and a complementary diagnosis of shoulder dysfunction and a group with pain and without a complementary diagnosis of shoulder dysfunction, the groups underwent initial evaluation, the exercise of preferential direction was identified, after rest they performed a series of 10 repetitions of the exercise, and then a new electromyographic reassessment. The second article had as objectives to verify if the exercise of preferential direction in the cervical spine promotes reduction of muscular activity and delay in the activation of the upper trapezius muscle after a week and a month of intervention in individuals with shoulder pain, to verify the size of the effect in the activity of the muscles after the exercise of preferential direction in the cervical spine and if it decreases the intensity of pain, functional incapacity, fear of movement and central sensitization through evaluation questionnaires. We selected 9 individuals with shoulder pain complaints over one week who performed cervical exercises daily, 4 sets of 10 repetitions distributed throughout the day and were reevaluated after one week and one month. In both articles, electromyography was used to evaluate the anterior deltoid, medial deltoid, upper trapezius and middle trapezius muscles. Samples were collected in the active movement and isometry in the abduction of the shoulder up to 80 ° in the scapular plane and also the maximum voluntary isometric contraction (MVIC) of each muscle to normalize the activity. For the first article we conclude that there was no immediate change in the activity of the anterior and middle fibers of the deltoid muscle and upper and middle fibers os the trapezius muscle and in the muscle activation sequence of patients with shoulder pain in this study. And no difference was found in muscle activity and in the activation sequence of these muscles between the groups with and without diagnosis by complementary tests of shoulder dysfunction. For the second article, we conclude that the preferential cervical spine exercise promoted a significant reduction of upper trapezius muscle activity, but did not interfere with its activation after one month of intervention in a sample of individuals with chronic shoulder pain. And the preferential direction exercise for the cervical spine promoted a very large effect size for the upper trapezius muscle and am average effect for the anterior deltoid muscle, both between one week and one month of exercise, and also decreased pain intensity, disability and central sensitization in individuals with shoulder pain.